Economic development, attitudes towards migration and the (lack of) willingness to help refugees: insights from the Aurora Humanitarian Index. (15th March 2021) - Jacobs, Dirk
ABSTRACT: In this paper Jacobs examines the connection between attitudes on migration, perceived threats linked to migration and the (lack of) willingness to help refugees using a data set of twelve countries from a survey project called the Aurora Humanitarian Index. The higher the perceived ethnic threat (economic, cultural or religious), the less willing individuals are to mobilize for refugees. In addition to patterns on the individual level, we examine the impact of country characteristics (gross domestic product (GDP), number of migrants and so on) through correlational and multilevel analysis. While neither the proportion of migrants nor the proportion of refugees impacts on the willingness to mobilize in favour of refugees, the economic situation does have an effect. In richer countries there is less willingness to help. Furthermore, we can observe that the effect of both opposition to migration and the perception of refugees as posing an economic threat is exacerbated in richer countries (countries with a higher GDP).